Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The central shrine consists of garbhagriha (sanctum sanctorum), antarala (vestibule or antechamber) and mukhamandapa (front porch). The shikhara (superstructure) of the shrine is only partially preserved. While the jangha (wall) of the garbhagriha is decorated with icons and sculptures, the mandapa is decorated with geometric, floral patterns and kirtimukhas (face of glory). The broken shikhara of the temple is of the shekhari (multi-spire) variety. The aedicules of the shikharas have gavaksha (dormer windows) designs on their surface.